Patient safety: knowledge of the caregiver (Research, Society and Development, 2022)
Introduction: The occurrence of adverse events increases the time and cost of hospitalization. The lack of knowledge on the subject prevents the caregiver from intervening in the prevention of damage. Methodology: A descriptive and cross-sectional study was carried out with 101 caregivers of hospitalized patients, including companions, family members and professional caregivers. The research was carried out at Hospital São Luiz – HSLZ, located in the municipality of São José de Ribamar-Maranhão. Result: This study evaluated the caregiver's knowledge and understanding of the booklet “How Can I Contribute to Increasing Patient Safety? Guidance for patients, families and caregivers. The age group from 40 to 59 years was the most prevalent, 81.19% of the sample was female, 50.50% brown, 43.56% married, 43.56% had completed high school and 37, 62% were children. Discussion: The caregiver profile found in the results of these studies is similar to that found by this researcher, with 81.19% of this segment being women, 37.62% daughters of the patients, 43.56% had attended high school, only 1.98% were professional caregivers. Despite the WHO recommendations on the need to involve patients and caregivers in their safety, it is not all phases of care where this becomes relevant. In addition, 76.24% were unaware of the booklet and 84.16% were unaware of the National Patient Safety Policy. Conclusion: In addition, the data encourage reflection on the profile of the caregiver who is present next to the patient. It is concluded that the language of the booklet is accessible, however, caregivers need further clarification on the subject.